Transnational connections, competences and identities: experiences of Chinese international students after their return ‘home’ - Gu, Qing; Schweisfurth, Michele (Wiley, 2015)
International students constitute a substantial and growing mobile population globally. However, as yet, the experiences of returnees and the ways in which their overseas studies impact on their identity and professional and personal lives over time have been under-researched areas. In this article we employ concepts from theories of transnationalism as a framework for the analysis of the experiences of Chinese graduate returnees. The empirical basis for the article is a 20-month, two-stage, mixed-method study of 652 Chinese students who returned home for work on completion of their degrees in UK universities over the last 25+ years. Evidence suggests that their journeys of studying abroad and returning home are dynamic and interconnected transnational experiences. Such experiences are avenues for diverse social networks that reinforce a complex cosmopolitan identity and awareness. They are, also, avenues for transnational(ised) new competences, skills and worldviews, which are increasingly valued by the students themselves upon return home. Irrespective of differences in their demographics and backgrounds, studying and living abroad was perceived by most returnees in our research as a profound identity transformating experience. These new connections, competences and identities enabled them to view and live life with a new sense of self at ‘home’ and, as a result, function in ways that continued to distinguish themselves from those around them over time. The findings have implications for higher education institutions and agencies that are concerned with enhancing the quality of university internationalisation. They also have implications for a broadened empirical and conceptual understanding of transnationalism.